La sapienza giuridica dell’anziano nella elaborazione romano-canonistica - Ventrella Mancini, Carmela (Quaderni di diritto e politica ecclesiastica, 2023)
From the history of ancient Rome to the modern codifications of the Latin Church, in the development of centuries-old experiences of several countries, the senile age has represented a recurring theme of study and juridical reflection, placing itself from time to time, under many profiles, as a boundary dictated from human nature, necessary for the exercise of specific rights and access to certain prerogatives. This contribution intends to dwell on the main stages of the historical evolution of complex perspectives and visions, not without contradictions, from antiquity to today’s orientations of the pontifical magisterium, aimed at enhancing the central role of the person even in mature age and his contribution to the contemporary world, especially in terms of wisdom and full participation in the life of contemporary societies.